UPAYA PENCEGAHAN COVID-19 DI DESA LEMPUYANG KECAMATAN SERANG KABUPATEN SERANG PROVINSI BANTEN TAHUN 2020 - Umar, Ernawati; Hamdiah, Dedeh; suryati, Eti (Universitas Sultan Ageng Tirtayasa, 2021)
The coronavirus pandemic, occurred between the end of 2019 and 2020. The outbreak claimed many lives.Humanity tries to find a solution to solve this problem. One solution that has emerged is to do social distancing,physical distance, wash your hands frequently with soap, and use a mask when you are outside the house orkeep using a mask if you cough.Purpose, this community service is to prevent the spread and transmission ofCovid-19 in the community in Lempuyang village.Method, In this community service the method used is mobileand offline education by paying attention to health protocols, as well as a simulation of how to wash hands 6steps in running water.The Results, achieved were a change in the knowledge of the people of LempuyangVillage, which at first was 81.7% less knowledgeable, after education had less knowledge, 43% left, thecommunity had worn masks when they were outside the house and crowded, and Untirta's donated portablewastapel could be used. In this community service the method used is mobile and offline education by payingattention to health protocols, as well as a simulation of how to wash hands 6 steps in running water.